"I didn't say that": Discursive evasion and responsibility management in political crisis communication (A forensic linguistic multiple-case study) - Nur Lailiyah; Kastam Syamsi; Ahmad Syafiq Amir Abdullah Zawawi (NOTION: Journal of Linguistics, Literature, and Culture, 2026)
Political leaders’ responses to crises often combine apology, denial, and ambiguity, raising questions about how responsibility is linguistically managed. While prior studies have focused on the effectiveness of political apologies, fewer have examined how accountability is constructed at the micro-linguistic level. This study addresses that gap by analyzing six high-profile political crisis responses from Indonesia, the United States, South Korea, and the United Kingdom using a qualitative multiple-case approach grounded in forensic linguistics and critical discourse analysis. The analysis focuses on selected linguistic features: passive constructions, nominalization, pronoun use, and metadiscursive refutation to identify patterns in how responsibility is expressed or obscured. The findings reveal three recurring strategies: (1) obscuring agency through passive and abstract forms, (2) diffusing responsibility through shifts between “I” and “we,” and (3) reframing statements to challenge interpretation or intention. These strategies appear consistently across cases, although their use reflects different political and cultural contexts. This study contributes by offering a clear, integrated analytical framework for examining responsibility management in political crisis discourse. Unlike previous research that emphasizes outcomes or rhetorical effectiveness, this study highlights how grammatical and discursive choices systematically shape representations of accountability. The findings provide practical insights for forensic linguistic analysis and support critical media literacy by showing how language can strategically negotiate responsibility in public communication.